2004
DOI: 10.1111/j.1523-1755.2004.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spironolactone on K+ homeostasis and ENaC expression in lymphocytes from chronic hemodialysis patients

Abstract: Spironolactone may be considered for the treatment of selected chronic HD patients. The effect of the drug on a known target of aldosterone, the ENaC, demonstrates the effectiveness of the drug to block aldosterone effects in nonepithelial tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…After full-text screening, one article was excluded as no data of serum potassium for the control group was provided. 21 Eleven studies were reported in this systematic review, among which five studies were RCTs [22][23][24][25][26] and six were non-randomized studies [27][28][29][30][31][32] ( Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After full-text screening, one article was excluded as no data of serum potassium for the control group was provided. 21 Eleven studies were reported in this systematic review, among which five studies were RCTs [22][23][24][25][26] and six were non-randomized studies [27][28][29][30][31][32] ( Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…The studies that reported no significant difference between the MRA and placebo group used a rather low-dose of the MRA (no more than 25 mg daily of spironolactone or eplerenone). [25][26][27][28][29]31 In the trials that found a significant increase in the serum potassium level after administration of MRAs, large doses (50 mg thrice a week) of MRAs were used. 23,24,30,32 There was an exception, the trial conducted by Gross et al, 22 in which patients took spironolactone 50 mg twice daily for 2 weeks, and no significant increase in the serum potassium level was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our group with a similar protocol have shown the effectiveness of the protocol used in the study presented here. In fact, measurements of genomic epithelial sodium channel expression in lymphocytes were returned to normal levels with the use of spironolactone (32). In the study presented here, we performed monthly plasma potassium analysis and we have not observed hyperkalemic episodes during the 2 years of spironolactone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have indicated that 40% to 60% of chronic renal failure patients are hyperaldosteronemic. 40 Most reports prove that oxidative stress is present in end-stage renal disease patients, and oxidative stress would be a strong cofactor for the development of cardiovascular complications. 41 Considering the high prevalence of LVH in hemodialysis patients, our findings emphasize the need for clinical studies to determine the potential beneficial effects of MR blockade in patients with chronic renal failure.…”
Section: Perspectivesmentioning
confidence: 99%